Pomegranate's Ethnobotanical Significance especially in Maternal Health Care in Kotmomin, District Sargodha as well as its Antimicrobial and Enzyme Inhibition Activities - Shamim Akhtar, Summiya Kanwal, Nimrah Malik, Ifrah Asma, Farwa Anser, Faisal Imran, Najma Shaheen, Sidra Islam, Sana Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Plants are considered a divine blessing, with 80,000 species deemed essential for medicinal use due to their crucial role in human welfare and environmental balance. Ethnobotanical research underscores the economic, biological, and cultural ties between people and plants, aiding in biodiversity conservation and rational resource utilization. Medicinal plants, constituting 18.9% of total flora, have been pivotal in traditional medicine, addressing ailments and combating infectious diseases, alongside synthetic drugs. Pomegranate, an ancient fruit with therapeutic potential dating back millennia, exemplifies traditional remedies, utilized for various ailments such as dysentery, diarrhea, and microbial infections through decoctions and folk medicine practices.The survey revealed that Punica granatum (pomegranate) is commonly used for medicinal purposes by local people. Traditional uses include treating influenza, digestive disorders, cancer, diabetes, and various other ailments. Different parts of the plant, including the fruit, leaves, and seeds, are utilized for medicinal purposes. Traditional uses of pomegranate during and after pregnancy include consuming teas, decoctions, juices, and pastes for various health benefits.Extracts from different parts of Punica granatum were tested for their antimicrobial activity against bacterial and fungal strains. The leaf, stem, peel, and seed extracts exhibited varying degrees of antibacterial and antifungal activities against different strains. The antimicrobial activity was assessed using minimum inhibitory concentration (MIC) values, with ethanol, methanol, and water as solvents. Results showed promising antibacterial and antifungal properties of Punica granatum extracts, suggesting their potential as natural antimicrobial agents.The study also evaluated the enzyme inhibition activity of Punica granatum extracts against urease. Extracts from the root, leaves, stem, and seeds were tested for their ability to inhibit urease activity. The root and stem extracts showed significant antiurease activity, with varying inhibitory concentrations. Ethanol extracts generally exhibited stronger antiurease activity compared to methanol and water extracts.These findings demonstrate the diverse medicinal properties of Punica granatum, supporting its traditional use in healthcare systems and highlighting its potential for further pharmaceutical research and development.